2018
DOI: 10.1016/j.mayocpiqo.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Door-to-Reperfusion Time for Mechanical Thrombectomy With a Multitiered Notification System for Acute Ischemic Stroke

Abstract: ObjectiveTo reduce door-to-angiographic reperfusion (DTR) time to 120 minutes for patients presenting with acute ischemic stroke attributed to anterior circulation large-vessel occlusion amenable to endovascular mechanical thrombectomy.Patients and MethodsPatients treated with mechanical thrombectomy before (April 10, 2015, through April 11, 2016) and after (April 12, 2016, through May 10, 2017) implementation of a multitiered notification system were studied. Lean process mapping was used to assess inefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Ever since EVT has become standard care for patients with LVO stroke and its effect has been shown to be highly time-dependent ( 7), many studies have examined measures to improve EVT-related logistics inside the CSC, leading to a fairly streamlined in-hospital workflow (8)(9)(10)(11)(12)(13). However, the workflow prior to arrival at the CSC-pre-and interhospital workflow-has only recently started to gain attention (14-16), and is currently considered one of the main "bottlenecks" in acute stroke management (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since EVT has become standard care for patients with LVO stroke and its effect has been shown to be highly time-dependent ( 7), many studies have examined measures to improve EVT-related logistics inside the CSC, leading to a fairly streamlined in-hospital workflow (8)(9)(10)(11)(12)(13). However, the workflow prior to arrival at the CSC-pre-and interhospital workflow-has only recently started to gain attention (14-16), and is currently considered one of the main "bottlenecks" in acute stroke management (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Timely initiation of EVT is of vital importance, because it increases the chance of good clinical outcome (7). Multiple studies have reported in detail on EVT-related time intervals after arrival at the CSC, such as door-to-CT and door-to-groin time (8)(9)(10)(11), and innovations to shorten these time intervals have been studied and successfully implemented (9)(10)(11)(12)(13). In recent years, several measures to improve the prehospital and interhospital workflow prior to EVT have also been proposed (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…[13] Additional factors that augment the initiation of stroke treatment include rapid availability of IV tPA in the emergency department as well as organizing a large-vessel occlusion alert to simultaneously notify multiple key players in the event of an intracranial large-vessel occlusion. [14]…”
Section: Methodsmentioning
confidence: 99%
“…This is likely since our onset-to-recanalization time is prolonged with meantime 354.9 min (±173.9 SD). Some published results [24][25][26][27] show that good clinical outcomes may not be obtained even where TICI 2b/3 is achieved if the onset to recanalization time window is prolonged. Moreover, the present results show higher hemorrhagic transformation than previous data, [28] and there are only 44.2% of the patients in our study that have had good collateral status, which may also affect the clinical outcome.…”
Section: Factors Predicting Clinical Outcome Of Acute Ischemic Strokementioning
confidence: 99%